2004
DOI: 10.1007/s11661-004-0355-6
|View full text |Cite
|
Sign up to set email alerts
|

Study on notch fracture of TiAl alloys at room temperature

Abstract: In-situ observations of fracture processes combined with one-to-one observations of fracture surfaces and finite-element method (FEM) calculations are carried out on notched tensile specimens of twophase polycrystalline TiAl alloys. The results reveal that most cracks are initiated and propagated along the interfaces between lamellae before plastic deformation. The driving force for the fracture process is the tensile stress, which is consistent with a previous study. [1] In specimens with a slit notch, most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 13 publications
6
19
0
Order By: Relevance
“…The inverse ductility/K 1C relationship is also observed in this paper, showing a lower tensile ductility 15 higher fracture toughness of the coarser NFL microstructure (Table 3).…”
Section: The Reason For the Inverse Ductility/k 1c Relationshipsupporting
confidence: 81%
See 3 more Smart Citations
“…The inverse ductility/K 1C relationship is also observed in this paper, showing a lower tensile ductility 15 higher fracture toughness of the coarser NFL microstructure (Table 3).…”
Section: The Reason For the Inverse Ductility/k 1c Relationshipsupporting
confidence: 81%
“…In a previous work, 15 observing of surface fracture process of very thin specimens in situ, the present authors indicated that cracks prefer to initiate and propagate along lamellar interfaces, which are the weakest link in the near fully lamellar microstructure. The interlamellar strength was calculated to be less than 100 MPa and is significantly lower than the translamellar strength.…”
Section: Introductionsupporting
confidence: 48%
See 2 more Smart Citations
“…A diamond-coated blade cutting tool was used to cut the as-cast TiAl alloys into metallographic and compressive samples. The metallographic samples were polished and then etched in a solution of 10 vol.% HNO 3 , 5 vol.% HF, and 85 vol.% water [20]. X-ray diffraction (XRD) using a diffractometer (Siemens D5000) with Cu Kα anode (λ = 1.54056 Å) was used to identify the phases present in the samples.…”
Section: Experimental Set-upmentioning
confidence: 99%